Analysis of the Torsional Vibration Characteristic of Traction Drive Shafting System of EMU - Zhou Shengtong; Zhu Jingwei; Zhou Xinjian; Sun Yingchao (Jixie chuandong)
The torsional vibrations of traction drive shafting system of EMU is one of key factors on heavily influence the running smoothness,safety and reliability of high-speed train. The torsional vibrations of a typical traction drive shafting system of EMU are investigated. After a concise introduction,the traction drive shafting system is simplified and equivalent to a lumped-parameters model with five moment of inertias and four torsional stiffness coefficients. Then,considering the meshing relationship of driving and driven gears,an undamped free torsional vibration equation of this lumped model is established by using direct stiffness method. At last,the natural frequency and mode shapes of this shafting system are obtained with the help of MATLAB software. On the other hand,a MATLAB/Simulink simulation model is also constructed according to above lumped-parameters model equation. And subsequently,the acceleration and displacement Bode plots of shafting system are calculated from this simulation model,these amplitude-frequency results are very useful to verify the natural frequencies obtained directly from the lumped model equation. Results show that the established lumped mass model is available to simulate the torsional vibration characteristics of traction drive shafting system,and the torsional resonance and fatigue problems may mainly happen on the driving side of shafting system. The research works are very useful for the future study on the dynamic design and optimization of traction drive shafting system of EMU.